The Philippine Online News Headlines on COVID-19 Pandemic: An Interpersonal Metafunction Analysis - Kabigting, Ryan (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2020)
This paper carries on a tentative interpersonal metafunctional analysis of the interpersonal metafunction online news headlines about COVID-19 pandemic. The analysis involved the differences in the mood type distribution, polarity, modality and other lexical characteristics. The findings reveal the dominance of the declarative mood texts tells the particular function of the online news headlines. It's informing the readers, rather than questioning or demanding them. Positive declarative clauses should convey information and convince readers with positive facts. A negative polarity does not imply a negative impression but confirms that a certain issue is inconsistent with what has become apparent. The use of “must” indicates that the speaker has a firm and strong conviction about a particular issue and that the readers are obliged to take the necessary steps in connection with what is believed. Word choices and the clause structure reflect the context of the texts and not the mood adjuncts or the modal verbal operators. Analysis of the functional structural mood text is very useful for understanding the interpersonal relationships between participants.